2016
DOI: 10.1111/aogs.13051
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of progression to severe disease in women with late preterm hypertensive disorders of pregnancy

Abstract: In women with non-severe hypertension in pregnancy near term, progression to severe disease can be predicted. This model requires external validation before it can be applied in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
2
7
0
2
Order By: Relevance
“…The degree of proteinuria cannot be used as a single indication for termination of pregnancy, but it can still reflect renal damage, and large amounts of proteinuria can lead to hypoalbuminemia, thereby affecting the outcome of PE. Increasing age was a risk factor for adverse perinatal outcomes in our study (OR: 1.072, 95% CI: 1.015-1.132), which was the same as other studies (6,7). Study had shown that in women ≥35 years old, the risk of adverse outcomes such as stillbirth, preterm birth and low birth weight was higher than that in the control group (20-34 years old) (42).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The degree of proteinuria cannot be used as a single indication for termination of pregnancy, but it can still reflect renal damage, and large amounts of proteinuria can lead to hypoalbuminemia, thereby affecting the outcome of PE. Increasing age was a risk factor for adverse perinatal outcomes in our study (OR: 1.072, 95% CI: 1.015-1.132), which was the same as other studies (6,7). Study had shown that in women ≥35 years old, the risk of adverse outcomes such as stillbirth, preterm birth and low birth weight was higher than that in the control group (20-34 years old) (42).…”
Section: Discussionsupporting
confidence: 88%
“…Other factors in the prediction model of maternal outcomes are SBP, AST, CR, and ALB. The results of our model are consistent with those of some established models (4)(5)(6)(7)(8)(32)(33)(34), indicating that elevated SBP, AST, and CR levels as well as reduced ALB levels predict the increase of adverse maternal outcomes, so changes in these indicators need to be closely monitored during clinical treatment. Other factors in the prediction model of perinatal outcomes were maternal age, HB, BMI, and proteinuria.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The characteristics of study populations showed that pregnant women and fetuses or newborns were the populations of most studies developed using LR and non-LR models, respectively. Among pregnant women, the LR algorithm was mostly applied to develop predictions for outcome categories of obstetric labor (13/77, 17%) [36,46,47,54,57,62,64,70,83,86,91,97,103], pregnancy-induced hypertension (12/77, 16%) [30,31,43,48,55,65,66,68,76,81,93,105], and gestational diabetes (7/77, 9%) [33,45,49,84,94,100,104]. Among fetus or newborn populations, non-LR algorithms were mostly applied to develop predictions for outcome categories of premature birth (12/50, 24%) [111,112,115,116,118,119,121,122,125,130,141,143] and fetal distress (9/50, 18%) [113,…”
Section: Lr and Other Machine Learning Algorithmsmentioning
confidence: 99%